La aplicación del currículo de primer año y su incidencia en el aprendizaje de los niños y niñas de primer grado de educación general básica de la escuela Juan Pablo II, de la ciudad de Quito. Período lectivo 2013–2014. Lineamientos alternativos - Villamarin Maldonado, Karina Isabel (2014)
The present study titled : " THE APPLICATION OF CURRICULUM FIRST YEAR AND ITS IMPACT ON LEARNING CHILDREN FIRST DEGREE GENERAL EDUCATION BASIC SCHOOL " John Paul II " , DE QUITO . LECTIVO PERIOD 2013 - 2014 " . ALTERNATIVE GUIDELINES . It is structured on the basis of current guidelines Graduation at the National University of Loja. The general aim of the research process was guided determine the incidence Curriculum First Year in the development of Learning children of "Juan Pablo II " of the city of Quito. 2013-2014 school . The methods used were : Scientist, Inductive, Deductive , Descriptive , and Statistical Model . The techniques applied were: Survey aimed at teachers of First Grade Students General Education " Juan Pablo II " School to establish the application of the First-Year Curriculum in daily work with children and , Testing Basics . Adaptation " Reea " applied to children of First Grade Basic General Education of " John Paul II " School of Quito , to assess learning . App Survey the teachers found that : 100% of the teachers surveyed itself applies Curriculum First Year General Education Core in the daily work with children. According to Test Basics " REEA " the following result was obtained : 76% of boys and girls has investigated positive variables with more than 64% , equivalent to a Satisfactory learning; 64 % have negative variables between 0 and 25 % , equivalent to 24% Satisfactory learning presents positive variables between 0 and 25 % Unsatisfactory learning equivalent to a 24% negative variables has more than 50 %, equivalent to a learning Unsatisfactory , 0% positive variables presented between 25 and equivalent to 50 % Unsatisfactory , and 12 % have negative variables between 25 and 50 % equivalent to Unsatisfactory